The Impact of Physical Activity and Dietary Measures on the Biochemical and Anthropometric Parameters in Obese Children. Is There Any Genetic Predisposition? - Zlatohlávek, Lukáš; Hubáček, Jaroslav Alois; Vrablík, Michal; Pejšová, Hana; Lánská, Věra; Češka, Richard (Central European journal of public health, 2015)
AIM: The aim of the study was to monitor the importance of laboratory, anthropometric and genetic determination of the presence of risk factors for atherosclerosis, obesity, dyslipidemia and components of the metabolic syndrome in obese children and the response to dietary and regimen interventions in obese children. METHODS: As a part of the study, 353 paediatric patients (46% boys, 54% girls) with obesity and dyslipidemia, aged 8-16 years, participated in a one-month lifestyle intervention programme. The programme involved a reduction of energy intake and supervised exercise programme consisting of 5 exercise units per day, each 50 minutes long. Standard biochemical methods were applied, including Lp-PLA2, as were anthropometric measurements and genetic analyses. RESULTS: During the reduction programme for the children there was a statistically significant decrease in all anthropometric indicators of bodyweight (p<0.001) as well as in lipid parameters and LpLPA2. Carriers of the FTO GG genotype and/or MC4R CC genotype lost significantly more body weight in comparison to non-carriers. CONCLUSION: Child obesity is an important social issue. After regimen interventions, there is weight loss as well as an improvement in biochemical parameters. There are individuals with a genetic predisposition for obesity, as well as individuals with a better response to regimen interventions which could, among other things, be determined by the FTO and MC4R genotypes.
Keywords: Genetic Predisposition to Disease; životní styl; risk factors; genotyp; receptor melanokortinový typ 4; Metabolic Syndrome; proteiny; mladiství; Česká republika; Genotype; genetic predisposition; mužské pohlaví; energetický příjem; Energy Intake; Life Style; ateroskleróza; Pediatric Obesity; regimen intervention; Czech Republic; Atherosclerosis; Dyslipidemias; dítě; Child; gen pro FTO; child obesity; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; dyslipidemie; ženské pohlaví; Anthropometry; metabolický syndrom; Humans; Receptor, Melanocortin, Type 4; Proteins; antropometrie; rizikové faktory; genetická predispozice k nemoci; Female; Risk Factors; Adolescent; obezita dětí a dospívajících; lidé; Male